-
Notifications
You must be signed in to change notification settings - Fork 1
/
Copy pathWeierstrass_normal_form.tex
129 lines (103 loc) · 6.35 KB
/
Weierstrass_normal_form.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
\documentclass{article}
\usepackage[utf8]{inputenc}
\usepackage{amsmath}
\usepackage{amsfonts}
\title{Weierstrass normal form}
\author{Dave Neary}
\date{May 2021}
\begin{document}
\maketitle
\section{Weierstrass normal form for cubic equations}
Given a general cubic equation
\[ ax^3 +bx^2y +cxy^2 + dy^3 +ex^2 + fxy +gy^2 + hx + iy +j = 0 \]
we can perform a set of substitutions to convert the equation to a form called Weierstrass normal form:
\[ Y^2 = X^3 + AX^2 + BX + C \]
or, equivalently:
\[ Y^2 = X^3 + \alpha X + \beta \]
In particular, for the cubic equation $C$:
\[u^3+v^3=\alpha \]
we can use the substitutions
\[x = \frac{12\alpha}{u+v}, y = 36\alpha\frac{u-v}{u+v} \]
to convert this equation to the form $C'$:
\[ y^2 = x^3 - 432 \alpha \]
This process can be inverted, so from any point $(x,y) \in C'$ we can generate a point $(u,v) \in C$ by the transform:
\[u = \frac{36\alpha +y}{6x}, v = \frac{36\alpha - y}{6x} \]
By this means, if we find rational points on either curve, we can generate a rational point on the other by this bijection.
This transformation might seem like magic, but we can work through this process if we have a rational point on the homogeneous projective form of original curve. To get to this form, we replace $u = \frac{U}{W}, v = \frac{V}{W}$ and multiply across by $W^3$ to give:
\[ U^3 + V^3 - \alpha W^3 = 0 \]
The point in $\mathbb{P}^2$ $P = [-1; 1; 0]$ is on the curve $C$. Since $W=0$ this corresponds to a point at infinity - a tangent point of the curve. The tangent at the point $P$ is given by the line:
\[ U \frac{\partial C}{\partial U} (P) + V \frac{\partial C}{\partial V} (P) + W \frac{\partial C}{\partial W} (P) = 0 \]
\[ \frac{\partial C}{\partial V} = 3V^2, \frac{\partial C}{\partial U} = 3U^2, \frac{\partial C}{\partial W} = 3\alpha W^2 \]
So at the point $P = [-1;1;0]$ the tangent line in $\mathbb{P}^2$ is $3U + 3V = 0$ (and we can divide out the common factor of 3).
Examining the curve $u^3+v^3=\alpha$ we can see that this does not intersect at all in the
real numbers, and has a triple root at the point at infinity. We will use this line as our
$Z=0$ axis after our transformation.
We will take $U-V=0$ as our $X$ axis, motivated by the fact that this is a line of symmetry
of our curve, and finally we will take $U+V-W = 0$ as our $Y$ axis, motivated by the fact
that it intersects $Z=0$ at $P$, and is helpfully orthogonal to the $X$ axis, so we should
avoid any pesky $XY$ terms after transformation.
Putting this together, our transformation from $(U,V,W)$ space to $(X,Y,Z)$ space will be:
\[
\begin{pmatrix} 1 & -1 & 0 \\ 1 & 1 & -1 \\ 1 & 1 & 0 \end{pmatrix}
\begin{pmatrix} U \\ V \\ W \end{pmatrix} =
\begin{pmatrix} X \\ Y \\ Z \end{pmatrix} \]
This matrix is, by design, invertible. Its inverse is:
\[ A^{-1} = \frac{1}{2} \begin{pmatrix} 1 & 0 & 1 \\ -1 & 0 & 1 \\ 0 & -2 & 2 \end{pmatrix} \]
This gives us an affine transformation which allows us to go from $(X,Y,Z)$ space to $(U,V,W)$ space as follows:
\begin{equation*}
\begin{split}
U &= \frac{1}{2}(X + Z) \\
V &= \frac{1}{2}(-X + Z) \\
W &= -Y + Z
\end{split}
\end{equation*}
By substituting these equations back into our homogeneous version of $C$, we get:
\[ \left(\frac{1}{2}(X + Z)\right)^3 + \left(\frac{1}{2}(-X + Z)\right)^3
- \alpha\left(-Y + Z\right)^3 = 0 \]
Expanding and cancelling terms, we simplify our original equation to:
\begin{equation*}
\begin{split}
\frac{1}{8}(6X^2Z + 2Z^3) - \alpha (-Y^3 + 3Y^2Z - 3YZ^2 + Z^3) &= 0 \\
3X^2Z + Z^3 + 4 \alpha Y^3 - 12 \alpha Y^2Z + 12\alpha YZ^2 - 4\alpha Z^3 &= 0
\end{split}
\end{equation*}
Replacing $x=\frac{X}{Z}, y=\frac{Y}{Z}$ to dehomogenize, we get:
\[ 3x^2 + 1 + 4 \alpha y^3 - 12 \alpha y^2 + 12\alpha y - 4\alpha = 0 \]
\[ 3x^2 = -4\alpha y^3 + 12\alpha y^2 -12 \alpha y +4 \alpha -1 \]
We want a perfect square term on the left, and a leading perfect cube on the right. We can achieve
this by multiplying both sides by $3^3\cdot4^2\cdot \alpha^2 = 432\alpha^2$:
\[ 3^4 4^2 \alpha^2 x^2 = -3^3 4^3 \alpha^3 y^3 + 3^3 4^3 \alpha^3 (3y^2) - 3^3 4^3 \alpha^3(3 y) +3^3 4^3 \alpha^3 - 432\alpha^2 \]
Substituting $a=36\alpha x, b=-12\alpha(y-1)$ we get:
\[ a^2 = b^3 - 432\alpha^2 \]
The transforms from $(a,b)$ to $(u,v)$ are now straightforward to derive:
\begin{equation*}
\begin{array}{llll}
a & = & 36\alpha x & \quad \mathrel{\#} \text{Final substitution above} \\
& = & 36 \alpha \frac{X}{Z} & \quad \mathrel{\#} x = \frac{X}{Z} \\
& = & 36 \alpha \frac{U-V}{U+V} & \quad \mathrel{\#} X = U - V, Z = U + V \\
& = & 36 \alpha \frac{u-v}{u+v} & \quad \mathrel{\#} u = \frac{U}{W}, v = \frac{V}{W} \\
b & = & -12 \alpha (y-1) & \quad \mathrel{\#} \text{Final substitution above} \\
& = & -12 \alpha \left(\frac{Y}{Z} - 1 \right) & \quad \mathrel{\#} y = \frac{Y}{Z} \\
& = & -12 \alpha \left(\frac{U+V-W}{U+V} - 1 \right) & \quad \mathrel{\#} Y = U+V-W, Z= U + V \\
& = & -12 \alpha \left(\frac{-W}{U+V}\right) & \quad \mathrel{\#} \text{Simplify } \frac{U+V}{U+V}=1 \\
& = & \frac{12 \alpha}{u+v} & \quad \mathrel{\#} u = \frac{U}{W}, v = \frac{V}{W}
\end{array}
\end{equation*}
The transformation from $(u,v)$ to $(a,b)$ is similar:
\begin{equation*}
\begin{array}{llll}
u & = & \frac{U}{W} & \quad \mathrel{\#} \text{Homogenization of original cubic curve} \\
& = & \frac{\frac{1}{2}(X + Z)}{-Y + Z} & \quad \mathrel{\#} U = \frac{1}{2}(X + Z), W = -Y + Z \\
& = & \frac{\frac{X}{Z} + 1}{-2\frac{Y}{Z} + 2} & \quad \mathrel{\#} \text{Division by Z in numerator and denominator} \\
& = & \frac{(x + 1)}{-2(y - 1)} & \quad \mathrel{\#} x = \frac{X}{Z}, y = \frac{Y}{Z} \\
& = & \frac{(\frac{a}{36\alpha} + 1)}{-2\left(\frac{-b}{12\alpha} \right)} & \quad \mathrel{\#} a = 36 \alpha x, b = -12 \alpha (y-1) \\
& = & \frac{a + 36\alpha}{6b} & \quad \mathrel{\#} \text{Simplify fraction} \\
v & = & \frac{V}{W} & \quad \mathrel{\#} \text{Homogenization of original cubic curve} \\
& = & \frac{\frac{1}{2}(-X + Z)}{-Y + Z} & \quad \mathrel{\#} V = \frac{1}{2}(-X + Z), W = -Y + Z \\
& = & \frac{-X + Z}{-2Y + 2Z} & \quad \mathrel{\#} \text{Simplify fraction} \\
& = & \frac{-x + 1}{-2(y -1)} & \quad \mathrel{\#} x = \frac{X}{Z}, y = \frac{Y}{Z} \\
& = & \frac{-\frac{a}{36\alpha} + 1}{-2(\frac{-b}{12\alpha})} & \quad \mathrel{\#} a = 36 \alpha x, b = -12 \alpha (y-1) \\
& = & \frac{-a + 36\alpha}{6b} & \quad \mathrel{\#} \text{Simplify fraction}
\end{array}
\end{equation*}
\end{document}